Analisis Efektifitas Aplikasi SIATAP Pada Biro Sumber Daya Manusia Kantor BPIP - Dilan Arya Saputra; Henry Eryanto; Muhammad Ikhwan (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the effectiveness of the SIATAP application in the Human Resources (HR) Bureau of the Pancasila Ideology Development Agency (BPIP). This study used a qualitative approach, collecting data through interviews with four informants directly involved in the use of the SIATAP application. The results indicate that the SIATAP application has been quite effective in supporting personnel administration management. This system is able to improve work efficiency, accelerate administrative processes, and enhance the accuracy and transparency of employee data. Furthermore, SIATAP also contributes to increased productivity and service quality within the HR Bureau. However, the effective implementation of SIATAP still faces several obstacles, such as dependence on internet connections and central servers, suboptimal integration with other systems, and differences in user understanding of how to operate the application.